Wild rabies virus detection by plaque assay from naturally infected brains in different species - Cardoso, T.; Pilz, D. (Elsevier B.V., 2004)
A simple, sensitive and specific plaque assay protocol for the detection of wild type rabies virus in different species is described using confluent monolayers of chicken embryo cells in 6-well plates. Plaques are produced after application of either agarose or Sephadex G-100 overlay onto cell monolayers and incubation for 96 h after virus infection at 37 degreesC. The parameters affecting plaque appearance include cell seeding concentration, overlay composition and time of incubation after infection. Optimal conditions are seeding at a concentration of 4 x 10(6) cell/cm(3), incubation at 37 degreesC in 5% CO2 atmosphere during 96 h, using either 1% agarose or 2% Sephadex G-100 overlays. The described plaque assay would be a new valuable too] in conducting various quantitative investigations, since the chicken embryo cells are susceptible to rabies virus infection from all species studied. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: rabies virus; plaque assay; chicken embryo related cells